’YOUNG GAS’ IN RIFT’S STRUCTURES OF UKRAINE - Guliy, V.; Poberezhs'ka, I.; Loktev, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Aim. Determination of space and genetic relationships between hydrocarbons concentrations and systems of mantle fractures and zones of modern and ancient rifts was purpose of conducted investigations. Methods. Geodynamics models of formation of main structural elements of Ukraine as well as analysis of rift structures of Ukraine, establishing of the most perspective among them with developed gas columns and real concentrations of hydrocarbons and deposits of ’young gas’ with evidences of new portions of hydrocarbon flows have been used in this investigations. Results. Analysis of geodynamic models and tectonic systematic of prospective rift structures of Ukraine with determination of their distribution in the limits of perspective sectors with industrial deposits of hydrocarbons has carried out. Importance of new portions of hydrocarbons flows, which increase real resources of deposits or keep its on relatively stable levels was shown. Scientific news. Character of relationships between occurrence of new industrial hydrocarbons deposits and specific conditions of rift structures formation as well as rhythmic features of portions of ’young gas’ have been established. Practical importance. Method of prognostic and possible localization of important industrial objects with hydrocarbons concentrations that can be use for exploration in gas-oil industry are discussed. Based on the geological models of formation of gas columns as stage of of hydrocarbon industrial field generation, combination of different geophysical methods has been proposed to establish real gas columns in sectors with different resources. It is possible only with using the methods of high resolution seismic and gravitational surveys. Additional supply of hydrocarbon resources aviliable by new portions of deep flows of ’young gas’ is proved.